2019
DOI: 10.5650/jos.ess18203
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of <i>Synechococcus</i> sp. VDW Cultivation with Artificially Prepared Shrimp Wastewater for Ammonium Removal and Its Potential for Use As a Biofuel Feedstock

Abstract: grow without using arable land. Moreover, algae can effectively capture carbon dioxide through photosynthesis and produce polysaccharides and triacylglycerol TAG. These compounds are the raw materials for production of bioethanol and biodiesel, which can be used in current engines without major modifications 2, 3. Although, many algae are accumulate significant quantities of TAG 20-50 of total dry weight and has potential as a raw material for biodiesel production than cyanobacteria, which typically store carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The marine cyanobacterium, Synechococcus sp. VDW, cultivated using shrimp wastewater exhibits a maximum productivity of 34 mg CDW/L/day over 7 days of cultivation (Srimongkol et al, 2019). Synechocystis 6803 cells can grow in a continuous cultivation system over a pH of 7.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…The marine cyanobacterium, Synechococcus sp. VDW, cultivated using shrimp wastewater exhibits a maximum productivity of 34 mg CDW/L/day over 7 days of cultivation (Srimongkol et al, 2019). Synechocystis 6803 cells can grow in a continuous cultivation system over a pH of 7.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…VDW (accession number MH393765) isolated from natural seawater in Thailand ( Tinpranee et al, 2018 ), we discovered that at optimum conditions (initial pH 7.4, inoculum size of 0.17 (OD 730 ), and ammonium concentration of 10.5 mg L −1 ), maximum ammonium removal and biomass productivity were 95% and 34 mg L −1d−1 , respectively. Furthermore, fatty acid methyl ester (FAME) analysis revealed that the major fatty acids were palmitic acid (C16:0), linoleic acid (C18:2 n6 cis), palmitoleic acid (C16:1), and oleic acid (C18:1 n9 cis), accounting for more than 80% of total fatty acids, indicating that this strain has potential for simultaneous water treatment and biomass production for biofuel feedstock ( Srimongkol et al, 2019b ). A review study by Pancha et al (2019) showed various microalgae lipid content cultivated in various wastewaters ranging from 18–79% w/w of biomass.…”
Section: Wastewater Integrated Algae-biorefinery For High-value Compo...mentioning
confidence: 99%
“…Moreover, analysis of fatty acid methyl esters (FAME) indicated that the predominant fatty acids, including palmitic acid (C16:0), linoleic acid (C18:2 n6 cis), palmitoleic acid (C16:1), and oleic acid (C18:1 n9 cis), constituted over 80% of total fatty acids. This composition highlights the strain's potential for simultaneous water treatment and biomass production for biofuel feedstock (Srimongkol et al, 2019b). A review by Pancha et al (2019) demonstrated that various microalgae cultivated in different wastewaters had lipid contents ranging from 18% to 79% w/w of biomass.…”
Section: Roles Of Microalgae-based Systems For Biofuel Biodiesel Bioe...mentioning
confidence: 90%